Advances and challenges in cancer immunoprevention and immune interception - Leisha A Emens; Sasha E Stanton; Philip E Castle; Shizuko Sei; Olivera J Finn (Journal for ImmunoTherapy of Cancer)
Invasive cancers typically evade immune surveillance through profound local and systemic immunosuppression, preventing their elimination or control. Targeting immune interventions to prevent or intercept premalignant lesions, before significant immune dysregulation has occurred, may be a more successful strategy. The field of cancer immune interception and prevention is nascent, and the scientific community has been slow to embrace this potentially most rational approach to reducing the global burden of cancer. This may change due to recent promising advances in cancer immunoprevention including the use of vaccines for the prevention of viral cancers, the use of cancer-associated antigen vaccines in the setting of precancers, and the development of cancer-preventative vaccines for high-risk individuals who are healthy but carry cancer-associated heritable genetic mutations. Furthermore, there is increasing recognition of the importance of cancer prevention and interception by national cancer organizations. The National Cancer Institute (NCI) recently released the National Cancer Plan, which includes cancer prevention among the top priorities of the institute. The NCI’s Division of Cancer Prevention has been introducing new funding opportunities for scientists with an interest in the field of cancer prevention: The Cancer Prevention-Interception Targeted Agent Discovery Program and The Cancer Immunoprevention Network. Moreover, the Human Tumor Atlas Network is spearheading the development of a precancer atlas to better understand the biology of pre-invasive changes, including the tissue microenvironment and the underlying genetics that drive carcinogenesis. These data will inform the development of novel immunoprevention/immuno-interception strategies. International cancer foundations have also started recognizing immunoprevention and immune interception with the American Association for Cancer Research, Cancer Research UK and the Society for Immunotherapy of Cancer each implementing programming focused on this area. This review will present recent advances, opportunities, and challenges in the emerging field of cancer immune prevention and immune interception.